Pemanfaatan Agregat Sungai Buri’ Kecamatan Rembon Sebagai Substitusi Agregat Kasar Dan Sabut Kelapa Sebagai Bahan Tambah Terhadap Kuat Tekan Dan Kuat Tarik Belah Beton - Prasetya, Megananda David; Setiawan, Arman; Lebang, Fauzy (Jurnal Penelitian Teknik Sipil Konsolidasi, 2023)
In the current technological era, concrete is one of the most widely used building materials in the world, including in Indonesia, therefore good quality concrete will greatly support structural safety. Indonesia is also a developing country that has quite advanced industrial prospects. Buri River gravel material in Rembon Sub-district is still abundant. To utilize this material, in this study it will be used as a substitute for coarse aggregate. And the addition of coconut fiber as a fiber to support the compressive strength of the concrete, resisting the tensile force. This research is an experiment conducted at the Makassar Concrete Bosowa Laboratory. The substitution of the 'river buri' stamps to be used is 25%, 50%, 75%, and 100%. As for the use of added coconut coir, constant 4% of the weight of cement in each substitution. From the results of the study with the substitution of 25%, 50%, 75%, and 100% with the addition of 4% coconut husk, the results were 25.64 Mpa, 25.93 Mpa, 26.11 Mpa and 26.40 Mpa. And the split tensile strength produced is 2.59 Mpa, 2.97 Mpa, 3.11 Mpa, and 3.23 Mpa